Korelasi Faktor Maternal (Usia, IMT, Gravida) dan Aktifitas Fisik terhadap Nyeri Punggung Selama Kehamilan pada Ibu Hamil Trimester III di TPMB Restu Bunda Gombong Kebumen - Sumarni Sumarni; Ossie Happinasari; Anjani Nur Anisa (Pusat Riset dan Inovasi Nasional, 2025)
Overview: Back pain during pregnancy is a common problem experienced by approximately 50–70% of pregnant women. Back pain during pregnancy is caused by an imbalance between the muscle activity in the lumbar region. Several maternal factors are known to play a role in the onset of back pain during pregnancy, including maternal age, body mass index (BMI), number of pregnancies (gravida), and physical activity. Research Method: This is a quantitative analytical study with a cross-sectional approach. The sample size was 33 pregnant women in their third trimester. The sampling technique used purposive sampling, and data analysis used the Chi-square test. Research Results: There was a relationship between BMI and back pain (p-value: 0.015), and there was no relationship between maternal age (p-value: 0.715), gravida (p-value: 0.442), and physical activity (p-value: 0.156) and back pain in pregnant women in their third trimester. Conclusion: There was a significant relationship between BMI and back pain in pregnant women in their third trimester, and there was no significant relationship between maternal age, gravida, and physical activity and back pain in pregnant women in their third trimester.